Unpacking Formative Assessment Literacy Among Teachers in Confucian Cultural Contexts: An Investigation in Online Learning Environments - Fu, Rong; Koh, Kim (Emerging Perspectives: Interdisciplinary Graduate Research in Education and Psychology, 2024)
This study critically examines the concept of formative assessment literacy within the realm of Confucian cultural contexts, particularly in the light of the widespread adoption of virtual learning platforms and online schooling post-COVID-19. Despite the universal expectation for teachers to develop sophisticated formative assessment literacy, formidable challenges persist, specifically in Confucian heritage countries in Asia, due to inadequate formative assessment literacy and limited professional development opportunities. This paper dissects the historical and cultural barriers preventing the implementation of formative assessment in these contexts, including ingrained hierarchies, traditional utilitarianism ethos, and rigorous conformity. The transition to online platforms has further complicated this landscape, underscoring the urgency of equipping teachers with skills to navigate and leverage new educational technologies effectively.